Yield Regulation in Kerala Forests - Iyppu, A. I.; Chandrasekharan, C. (Indian Forester, 1962)
General principles of yield regulation in forestry and its importance for sustained annual yield is discussed. Necessity of a reliable inventory in yield regulation is touched upon. Main methods of yield regulation under the major Silvicultural system. Followed in tbe State are dealt with in detail. Account is also given of the bamboo resource survey and fixation of sustained yield of bamboos for supply to the Rayon pulp factory in the Kozhikode circle. The practical difficulties met with in the execution of the prescriptions of the working plan in view of the ever increasing demand and the obligatory clearance for food production and five year plan projects are pointed out.